Investigating students’ concerns on the development of masterly! / Nurafrina Omar Bahsir and - Omar Bahsir, Nurafrina; Atan, Mohd Amirul (Academy of Language Studies, 2023)
Knowledge of grammatical rules is one of the important skills in the English language that needs to be mastered by students in order to score well in their studies. Additionally, the English language would be needed in many situations as the majority of colleges and companies contain a diverse range of cultures, religions, and learning styles, so the ability to engage effectively in diverse groups is one of the fundamental talents (Hashim & Leitner, 2014). Even though the English language is taught at all levels of education in Malaysia, it is found that Malaysian students are still quite left behind in their grammatical knowledge of the language. Thus, this study addresses these concerns by collecting feedback from the users regarding an e-exercise book entitled ‘MASTERLY!’ This exercise book consists of different levels of difficulty that test the users’ understanding in mastering the basic grammatical rules of English. An online survey questionnaire was used to collect the data from a total of 45 students from SMK Sultan Abdul Aziz Shah, Selangor, Malaysia. The researchers intend to further develop the e-exercise book and market it based on the feedback collected. According to the post-questionnaire survey, part of the feedback regarding the e-exercise book was that the notes section needed to address more details of the topic and that the exercises were too simple.